2008
DOI: 10.1063/1.2987424
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state spectroscopy on a quantum dot side coupled to a quantum wire

Abstract: We report excited-state spectroscopy on a quantum dot side-coupled to a quantum wire with accurate energy estimation. Our method utilizes periodic voltage pulses on the dot, and the energy calibration is performed with reference to the bias voltage across the wire. We demonstrate the observation of the orbital excited state and the Zeeman splitting in a single dot.Semiconductor quantum dots are promising candidates for quantum bits (qubits) [1]. In a conventional dot with two leads, the current through the dot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Our results are reproduced by a model that treats coupling of the detector to a discrete state, and are reminiscent of those in a spectroscopy study of deliberately formed quantum dots. 18 We report on the GaAs multi-QPC device of Ref. 16 ͓Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are reproduced by a model that treats coupling of the detector to a discrete state, and are reminiscent of those in a spectroscopy study of deliberately formed quantum dots. 18 We report on the GaAs multi-QPC device of Ref. 16 ͓Fig.…”
mentioning
confidence: 99%
“…To obtain this value we assumed ␤ = 1 2 , which should be reasonable since G d Ͼ 2e 2 / h. 19 ␥ is within the range reported in experiments on quantum dots formed by electrostatic gating. 18,20 In Fig. 3 we plot the differential conductance ͓g d ͑V s , V dc ͔͒ obtained by scanning V dc continuously, and in- crementing V s over the region near pinch off.…”
mentioning
confidence: 99%
“…3(b), (c), (d), we review energy spectrum measurement reported in Ref. 17. When V amp is small, g versus V Pc shows a series of dips like Fig.…”
Section: Experimental Demonstrationmentioning
confidence: 99%
“…The electrostatic potential of QD is detected through the conductance of a quantum point contact (QPC) placed on the other side of QD 13,14,15 . We first explain how the energy spectrum of QD (including excited states) is obtained in this device 16,17 . For the spectroscopy, the plunger gate voltage V P on QD is driven to oscillate as a rectangular wave with the amplitude V amp and the center voltage V Pc , as illustrated in Fig.…”
Section: Detection Principlementioning
confidence: 99%
“…21 The present measurement can therefore be applied to the case of finite source-drain bias voltage V sd of t-QPC with tuning the window to local chemical potentials. To investigate the polarization mechanism, we thus measure the variation of P versus V sd on 0.5 and 1.0 conductance plateaus.…”
Section: (C) When T-qpc Was Open (The Left Panel) I 0→2 I 1→3mentioning
confidence: 99%